Reliability of the CMT neuropathy score (second version) in Charcot-Marie-Tooth disease - Murphy, Sine´ad M. (2011)
The Charcot-Marie-Tooth neuropathy score (CMTNS) is a reliable and valid composite score comprising symptoms, signs, and neurophysiological tests, which has been used in natural history studies of CMT1A and CMT1X and as an outcome measure in treatment trials of CMT1A. Following an international workshop on outcome measures in Charcot-Marie-Tooth disease (CMT), the CMTNS was modified to attempt to reduce floor and ceiling effects and to standardize patient assessment, aiming to improve its sensitivity for detecting change over time and the effect of an intervention. After agreeing on the modifications made to the CMTNS (CMTNS2), three examiners evaluated 16 patients to determine inter-rater reliability; one examiner evaluated 18 patients twice within 8 weeks to determine intra-rater reliability. Three examiners evaluated 63 patients using the CMTNS and the CMTNS2 to determine how the modifications altered scoring. For inter- and intra-rater reliability, intra-class correlation coefficients (ICCs) were ≥0.96 for the CMT symptom score and the CMT examination score. There were small but significant differences in some of the individual components of the CMTNS compared with the CMTNS2, mainly in the components that had been modified the most. A longitudinal study is in progress to determine whether the CMTNS2 is more sensitive than the CMTNS for detecting change over time.